Dietary consumption of cruciferous vegetables and bladder cancer risk: A systematic review and meta-analysis - Yu, Pengkui; Yu, Lin; Lu, Yi (Frontiers in Nutrition, 2022)
Objective Previous studies on the association of cruciferous vegetables intake with bladder cancer risk have reported inconsistent results. We performed the present meta-analysis to summarize evidence on this association and to quantify the potential dose-response relation based on all available cohort studies. Methods A comprehensive literature search of relevant articles up to March 2022 was performed in PubMed and EMBASE. The summary risk estimates with 95% confidence intervals for the highest vs. the lowest intake of cruciferous vegetables were calculated. Dose-response meta-analysis was also performed for studies reporting categorical risk estimates for at least three quantitative levels of cruciferous vegetables intake. Results We found that the highest cruciferous vegetables intake was not significantly associated with a lower risk of bladder cancer, compared with the lowest cruciferous vegetables intake category (RR = 0.92, 95% CI 0.80–1.06). Linear dose-response meta-analysis indicated that the pooled RRs for 10 g/day or 1 servings/week increment of cruciferous vegetables intake was not significantly associated with a reduced risk of bladder cancer (P = 0.106 and P = 0.147, respectively). There was no evidence of significant publication bias either with Begg’s test (P = 0.386) or Egger’s test (P = 0.253). Conclusion The results of this study did not support the hypothesis that dietary cruciferous vegetables intake was associated with a lower risk of bladder cancer. Further large prospective cohort studies are warranted to confirm our preliminary findings.